Psychological Opportunities for Improving Interpersonal Relationships in Student Groups - Nurilla ugli, Shukrullayev Khamidulla (Jurnal Psikologi, 2025)
Interpersonal relationships and effective communication within student groups are of great importance for higher education institutions. Recent research highlights that by restructuring educational tasks, it is possible to enhance students’ communication skills and ability to express their ideas, ultimately improving the overall effectiveness of education. This study focuses on the psychological aspects of the formation of interpersonal relationships within the student environment, the influence of interaction methods, and the implementation of training programs. These are analyzed in the context of how training sessions and the structure of learning tasks contribute to the development of interpersonal communication skills among students.